Against Quantum Indeterminacy. (26th July 2017) - Glick, David
Abstract: A growing literature is premised on the claim that quantum mechanics provides evidence for metaphysical indeterminacy. But does it? None of the currently fashionable realist interpretations involve fundamental indeterminacy and the 'standard interpretation', to the extent that it can be made out, doesn't require indeterminacy either.